Viscosity of Binary Aqueous Solutions Involving Malonic, Maleic, Malic, Tartaric, and Citric Acids in the Temperature Range between 303 and 363 K: Experimental Data and Modeling - Savoldi A.L.L.* (2022)
© 2022 American Chemical Society.Kinematic viscosity is a key property for the design of flow systems. This transport property is directly dependent on temperature and concentration and indirectly dependent on molecular interactions that take place in a mixture. Carboxylic acids are a class of chemical compounds with employment in a large variety of processes and applications. The viscosity of carboxylic acid solutions changes due to the acid size and its concentration. The application of models can provide property prediction and generate information about molecular interactions in a mixture. This work studies the kinematic viscosity of binary aqueous solutions of carboxylic acids (malonic, maleic, malic, tartaric, and citric acids) at different temperatures (from 303.2 to 363.2 K with an increment of 10 K) and concentrations (from 0.5 to 3.0 mol·kg-1 with an increment of 0.5 mol·kg-1). The data were treated by the Eyring equation combined with the UNIFAC model. The experimental results and thermodynamic properties indicate that the kinematic viscosity is strongly influenced by the size of carboxylic acid and the molar mass of the binary solution. The suggested modeling showed capability of correlating the experimental data.